The Role of Caspase-1 and Caspase-4 in Modulating Gingival Epithelial Cell Responses to Aggregatibacter actinomycetemcomitans Infection - Kartheyaene Jayaprakash Demirel; Alessandra Neves Guimaraes; Isak Demirel (Pathogens)
Periodontitis is a chronic inflammatory disease characterized by bacterial infection and immune dysregulation. Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) is a key pathogen linked to disease progression. Caspase-1 and caspase-4 regulate inflammasome activation and cytokine release, yet their roles in gingival epithelial immunity remain unclear. The aim of this study was to elucidate the involvement of caspase-1 and caspase-4 in regulating the immune response to A. actinomycetemcomitans infection in gingival epithelial cells. Human gingival epithelial cells (Ca9-22) and caspase-1- and caspase-4-deficient cells were infected with A. actinomycetemcomitans for 24 h. Inflammatory mediator release was analyzed using Olink proteomics. Bacterial colonization and invasion were assessed using fluorescence-based assays and gentamicin protection assays. Caspase-1- and caspase-4-deficient cells showed significantly altered cytokine and chemokine profiles after infection with A. actinomycetemcomitans, showing reduced IL-17C and IL-18 release. We also found an increased release of TGF-α and LIF from caspase-4-deficient cells, along with elevated levels of the chemokines IL-8, CXCL9, and CXCL10. Additionally, both caspase-1- and caspase-4-deficient cells showed increased bacterial colonization and invasion, particularly in caspase-4-deficient cells. These findings suggest that caspase-1 and caspase-4 play distinct yet essential roles in gingival epithelial immunity, regulating cytokine release, barrier integrity, and defense against A. actinomycetemcomitans colonization.